2011
DOI: 10.1007/s12088-011-0081-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mineral Phosphate Solubilization on Biological Nitrogen Fixation by Diazotrophic Cyanobacteria

Abstract: The ability of two diazotrophic cyanobacteria Westiellopsis prolifica and Anabaena variabilis were examined to solubilize extracellular insoluble tricalcium phosphate (TCP) and Mussorie rock phosphate (MRP). The two strains exhibited a differential response to insoluble forms of phosphorus used. W. prolifica showed better growth in presence of MRP while A. variabilis proliferated better in presence of TCP. Biological nitrogen fixation measured in terms of acetylene reduction (AR) activity showed significant va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 9 publications
0
13
0
2
Order By: Relevance
“…Actinobacteria and Cyanobacteria were associated at high significance with DTP. Yandigeri et al [33] reported that Cyanobacteria were capable of dissolving inorganic phosphorus, and Streptomyces in Actinobacteria were capable of dissolving organic phosphorus. Therefore, from the results of this study, it is speculated that the changes in the overlying water DTP in Sancha Lake were partly due to the dissolution of inorganic and organic phosphorus by Actinobacteria and Cyanobacteria, respectively, releasing DTP into the overlying water.…”
Section: Resultsmentioning
confidence: 99%
“…Actinobacteria and Cyanobacteria were associated at high significance with DTP. Yandigeri et al [33] reported that Cyanobacteria were capable of dissolving inorganic phosphorus, and Streptomyces in Actinobacteria were capable of dissolving organic phosphorus. Therefore, from the results of this study, it is speculated that the changes in the overlying water DTP in Sancha Lake were partly due to the dissolution of inorganic and organic phosphorus by Actinobacteria and Cyanobacteria, respectively, releasing DTP into the overlying water.…”
Section: Resultsmentioning
confidence: 99%
“…The phosphate solubilizing microbes also facilitate growth through other mechanisms [138][139][140]35] as shown in Fig. 2.…”
Section: Exploitating the Microbes In P Nutritionmentioning
confidence: 99%
“…Despite these proposals, it is still ambiguous with regard to defi nite operative method of P solubilization by cyanobacteria. In a recent study, Westiellopsis prolifi ca and Anabaena variabilis were shown solubilize TCP and MRP (Yandigeri et al 2011 ). Further, it was demonstrated that P solubilization was due to the production and action of phthalic acid without any decrease in pH.…”
Section: Cyanobacteria P Solubilizationmentioning
confidence: 94%